2016
DOI: 10.1007/s11745-016-4160-y
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids Increase Intracellular Lipid Accumulation and Oxidative Stress by Modulating PPARα and SREBP‐1c in L‐02 Cells

Abstract: Excessive fat accumulation and increased oxidative stress contribute to the pathogenesis of nonalcoholic fatty liver disease (NAFLD). However, the mechanisms underlying the development of steatosis are not entirely understood. The present study was undertaken to establish an experimental model of hepatocellular steatosis with a fat overaccumulation profile in which the effects of oxidative stress could be studied in L-02 cells. We investigated the effects of free fatty acids (FFA) (palmitate:oleate, 1:2) on li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 31 publications
5
30
0
Order By: Relevance
“…The authors reported that high concentration of free fatty acid induced excessive lipid accumulation and oxidative stress by down-regulating the ppara expression, similar to our observations [49]. PPARα is nuclear hormone receptors, and regulates the expression of many genes involved in fatty acid oxidation, ketogenesis, gluconeogenesis, cholesterol catabolism, among others.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The authors reported that high concentration of free fatty acid induced excessive lipid accumulation and oxidative stress by down-regulating the ppara expression, similar to our observations [49]. PPARα is nuclear hormone receptors, and regulates the expression of many genes involved in fatty acid oxidation, ketogenesis, gluconeogenesis, cholesterol catabolism, among others.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, a study developed with a mammalian model of hepatocellular steatosis established the effects of free fatty acid and the mechanism associated to oxidative stress [49]. The authors reported that high concentration of free fatty acid induced excessive lipid accumulation and oxidative stress by down-regulating the ppara expression, similar to our observations [49].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, SREBP-1c and patatin-like phospholipase domain-containing protein 3 (PNPLA-3) pathways may affect the progression of NASH [39,40]. The pathway may be associated with inflammation [41] and oxidative stress [42]. PNPLA-3 has been reported to be related to the increase in the level of total glycerol and risk of hepatic injuries [43].…”
Section: Introductionmentioning
confidence: 99%
“…The L-02 cells were cultured in RPMI 1640 medium (Gibco, California, USA) supplemented with 10% fetal bovine serum (FBS) (Gibco, California, USA), 100 U/mL penicillin and 100 U/mL streptomycin (Gibco, California, USA) for 24 hours. All the cell lines were maintained at 37°C in a humidified incubator with an atmosphere of 5% CO 2 (Qin et al, 2016).…”
Section: Cell Culturementioning
confidence: 99%
“…Sodium palmitate and oleate (Sigma, New York, USA) were added to the H2O2 and NaOH solutions, respectively, and then, they were added to a 10% solution of fatty-acid-free bovine serum albumin (BSA) (Sangon Biotech, Shanghai, China), which was dissolved overnight at 55°C with gentle shaking; then, the mixture was cooled to room temperature, filtered and stored at 4°C in a refrigerator (Qin et al, 2016).…”
Section: Preparation Of Ffa Culture Mediummentioning
confidence: 99%